PENGARUH LINGKUNGAN KERJA, BUDAYA ORGANISASI, TERHADAP KOMITMEN ORGANISASI DALAM MENINGKATKAN KINERJA PEGAWAI PADA UPT PERPUSTAKAAN UNIVERSITAS JEMBER - Iswahyudi, Iswahyudi (BISMA: Jurnal Bisnis dan Manajemen, 2017)
Abstract: This research aims to know and analyze the effect of work environment, organizational culture to organization commitment increase performance of library employees at UPT Jember University. This research is using kind of explanatory research with kuantitative aapproach by sampel is performance of library employees at UPT Jember University as much forty tree (43) sampel. Primary fact is using kuesioner result obtainable from performance of library employees at UPT Jember University. Analyse tools which use in this research is correlation analyse by software SPSS 18. To analyse the causal relation between the variable and to verify reseach of simultan wilful so, analyse tools which using is assumsiont classic test. The result known that the work environment and organizational culture through organization commitment take effect performance of library employees At UPT Jember University by significant whre direct or indirect to performance of library employees at UPT Jember University. Result of this research support by some teories and consisten with before result of this research.Keywords: Work Environment, Organizational Culture, Organization Commitment and Performance of Library.